Cloud computing platforms for delivering computer science and mathematics instructional course content to learners - Chiroma, Haruna; Ahmad, Muhammad Murtala; Abdulhamid, Gazali Muhammed; Gital, Abdulsalam Ya'u; Abdullahi, Umar I.; Ibrahim, Adamu Abubakar; Shuib, Liyana (Institute of Electrical and Electronics Engineers Inc., 2018)
The cloud computing can be considered as a major driver in innovations and transformations in teaching and learning. The research on cloud computing in education is on the increase and is attracting the attention of researchers. In this paper, we designed and developed an integrated cloud computing learning platform based on Unified Modelling Language for delivering course contents of computer science and mathematics courses to learners. The propose cloud learning framework has the potentials for improving ubiquitous and learner centred learning activities. Educators can find the propose cloud learning platform useful for improving learning outcomes and motivation